VALUES OF ISLAMIC RELIGIOUS EDUCATION IN RELIGION-BASED VIDEO CONTENT ON TIKTOK - Imaniyah, Fina; Saifuddin; Rohmad, Muhammad Ali (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Education is not only aimed at improving students’ intelligence but also at building their character and morality. Thus, education is essential in producing individuals who are not only intelligent but also virtuous, capable of self control, and able to contribute beneficially to society. This study focuses on the religious values contained in the content of @kadamsidik00 as well as the methods of delivering religious messages through his video content. This research employs a qualitative approach with Library Research, obtained by comparing the information found with other relevant sources. The TikTok content of @kadamsidik00 contains values of Islamic Religious Education, including muamalah (social interactions), aqidah (faith), ibadah (worship), and akhlaq (morality). @kadamsidik00 utilizes communicative and reflective methods, with simple and contextual language.